2014
DOI: 10.17969/agripet.v14i2.1874
|View full text |Cite
|
Sign up to set email alerts
|

Kandungan Total Fungi Serta Jenis Kapang dan Khamir pada Limbah Pabrik Pakan yang Difermentasi dengan Berbagai Aras Starter ‘Starfung’

Abstract: This research was conducted to processed the waste feed into a feed mill potentially probiotic functional seen a total of fungi, molds and yeasts and the types of protein biomass increase. The material used in the study were the starter starfung, distilled water and waste feed mill feed. The tools used in the study were an oven, thermometer, drying cabinets, pH meters, moisture meter grand. Research using Rancangan Acak Lengkap (RAL) is 4 treatments with 4 replications. The treatment used T0 = Feed + (Starter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
5
0
1
Order By: Relevance
“…During the fermentation, changes in the growing of microorganism groups include yeast, molds, and LAB (Koesoemawardani et al, 2019a). This is in line with research conducted by Dewi et al (2014) which states that mold can grow in acidic conditions. Temperature can affect mold growth.…”
Section: Total Moldsupporting
confidence: 92%
See 1 more Smart Citation
“…During the fermentation, changes in the growing of microorganism groups include yeast, molds, and LAB (Koesoemawardani et al, 2019a). This is in line with research conducted by Dewi et al (2014) which states that mold can grow in acidic conditions. Temperature can affect mold growth.…”
Section: Total Moldsupporting
confidence: 92%
“…Fermentation time is a variable related to the microbial growth phase during the fermentation process so that it will affect the fermentation results. Several previous studies have shown that the duration of fermentation affects the physical, chemical, microbiological and sensory characteristics (Andarti & Wardani, 2015;Dewi et al, 2014;Moede et al, 2017;Mulyani et al, 2021;Pratomo et al, 2020;Suyatno et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…until neutral. Dewi et al (2014) stated that acidity conditions affect the development of fungi, fungi can grow optimally in acidic conditions and have a fairly wide pH range between 2-8. Factors that affect the total fungus in the chicken litter are temperature, humidity, substrate, and acidity.…”
Section: Total Fungimentioning
confidence: 99%
“…has a grey color and it has mycelium (stolons) and hyphae that are not septate or insulated (coenocytic hyphae). These hyphae will form rhizoids that stick to the growth medium (substrate) and turn into dark color when the fungus was going old (Dewi et al, 2014). The fungus Rhizopus sp.…”
Section: Introductionmentioning
confidence: 99%